2005
DOI: 10.1001/archpedi.159.5.470
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Refusal of Childhood Vaccines Among Parents of School-aged Children

Abstract: Continued efforts must be made to educate parents about the utility and safety of vaccines, especially parents requesting nonmedical exemptions to school immunization requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
345
6
15

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 475 publications
(399 citation statements)
references
References 21 publications
22
345
6
15
Order By: Relevance
“…However, other researchers have shown that even in states allowing religious exemptions only, an increasing number of parents who refuse to have their children vaccinated have secular reasons for their refusal, such as safety concerns about vaccines. 20,21 Our data showed that among states that did not grant exemptions for philosophical reasons, states with procedures that were "easy" had the highest exemption rates. 15 Complex procedures for applying for an exemption may discourage less steadfast religious objectors from acquiring exemptions in "medium" and "difficult" states.…”
Section: Discussionmentioning
confidence: 76%
“…However, other researchers have shown that even in states allowing religious exemptions only, an increasing number of parents who refuse to have their children vaccinated have secular reasons for their refusal, such as safety concerns about vaccines. 20,21 Our data showed that among states that did not grant exemptions for philosophical reasons, states with procedures that were "easy" had the highest exemption rates. 15 Complex procedures for applying for an exemption may discourage less steadfast religious objectors from acquiring exemptions in "medium" and "difficult" states.…”
Section: Discussionmentioning
confidence: 76%
“…1,2 Underimmunization has been associated with elevated risk of vaccine-preventable disease in individual patients. [3][4][5][6][7][8][9] Beyond individual risk, nonmedical immunization exemptions have been associated with increased community risk of measles and pertussis outbreaks. 4,6,10 For optimal public health and patient care, clinicians and health care systems ideally should tailor care to their communities.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Several studies have shown that a medical professional's recommendation to vaccinate is positively correlated with vaccination. [13][14][15][16] In our study, parents voiced high confidence in their doctor's recommendations. One parent said: " Doctor' s advice; it' s the best advice.…”
Section: Confidence In Health Care Providersmentioning
confidence: 61%
“…21 Compared with parents of vaccinated children, those of unvaccinated children are less likely to perceive vaccine-preventable diseases to be severe or believe that their own children are susceptible to these diseases. 13 Parents of unvaccinated American children also reported less trust in the government, the vaccine industry, and vaccine researchers. 13 Because of this distrust, some parents continue to voice concerns about vaccine safety even after these concerns have been scientifically refuted in large studies.…”
Section: Applying These Motivators To the United Statesmentioning
confidence: 99%
See 1 more Smart Citation